2020
DOI: 10.1177/0300060520936806
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the intestinal flora in patients with peripheral neuropathy associated with type 2 diabetes

Abstract: Objective To study the characteristics of the intestinal flora in patients with diabetic peripheral neuropathy (DPN) and analyze the association between the intestinal flora and clinical indicators. Methods We classified 80 subjects into three groups: patients with DPN (n = 45), patients type 2 diabetes without DPN (n = 21), and healthy controls (n = 14). The intestinal flora composition was compared among the three groups, and the correlation between the intestinal flora and clinical indicators was analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 27 publications
5
42
0
Order By: Relevance
“…Blautia and lactobacillus genera were enriched in participants with diabetes and were more abundant in the DM group than in the DR group. These increased Blautia and lactobacillus genera in diabetic patients were also observed in other studies ( Larsen et al., 2010 ; Karlsson et al., 2013 ; Wang et al., 2020 ). Wang et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Blautia and lactobacillus genera were enriched in participants with diabetes and were more abundant in the DM group than in the DR group. These increased Blautia and lactobacillus genera in diabetic patients were also observed in other studies ( Larsen et al., 2010 ; Karlsson et al., 2013 ; Wang et al., 2020 ). Wang et al.…”
Section: Discussionsupporting
confidence: 88%
“…These increased Blautia and lactobacillus genera in diabetic patients were also observed in other studies ( Larsen et al., 2010 ; Karlsson et al., 2013 ; Wang et al., 2020 ). Wang et al. (2020) reported that Blautia was positively correlated with tauroursodeoxycholic acid (TUDCA) levels.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, we examined the lipid metabolism of the three major species of Lachnoclostridium as we found a positive association with visceral fat, as well as several studies have reported it to be related to diet-induced obesity (Zhao L. et al, 2017;Li et al, 2019;Sun et al, 2020), total cholesterol and LDL-C (Wang et al, 2020). Additionally, the mechanisms by through Lachnoclostridium impacts obesity remain unknown.…”
Section: Discussionmentioning
confidence: 78%
“…Diabetic neuropathy has been linked to changes in the diversity of the gut microbiota and the increased presence of pathogens [ 81 ]. A comparison of the gut microbiota in patients with diabetic neuropathy, patients with diabetes without diabetic neuropathy and healthy individuals showed an increase in Firmicutes and Actinobacteria as well as a decrease in Bacteroidetes in patients with diabetic nephropathy when compared to patients with diabetes without diabetic neuropathy and healthy individuals.…”
Section: Gut Microbiota Type 2 Diabetes and Its Complicationsmentioning
confidence: 99%